Langerhans Cell Histiocytosis Involving the Thymus and Heart With Simultaneous Thymoma: A Case Report - Ji, Ting; Zhong, Yuxia; Cheng, Deyun (Frontiers in Oncology, 2022)
Langerhans cell histiocytosis (LCH) is a rare disease characterized by clonal expansion of CD1a+/CD207+ cells in lesions. The most frequent sites involved are bone and, less commonly, lymph nodes, lung, and skin. The thymus or heart is rarely involved with LCH. In this case, we present a 73-year-old female with a mediastinal mass. Histopathology after thymectomy identified this mass as type AB thymoma; notably, subsequent immunohistochemical tests showed lesions of LCH scattered in the region of thymoma. 18-Fluorodeoxyglucose positron emission tomography/computed tomography (18-FDG-PET/CT) was performed to make an overall assessment of the extent of this disease, which demonstrated suspicious cardiac involvement of LCH. This report highlights the importance of differentiating abnormalities of the thymus or mediastinal mass from LCH and the necessity of comprehensive evaluation for patients with LCH.